Trà My
17 tháng 12 2016 lúc 22:14

Vì \(\hept{\begin{cases}\left(x+2y-4\right)^2\ge0\\\left(2x-3y-1\right)^2\ge0\end{cases}}\)=> \(\left(x+2y-4\right)^2+\left(2x-3y-1\right)^2\ge0\)

\(\left(x+2y-4\right)^2+\left(2x-3y-1\right)^2=0\) <=> \(\left(x+2y-4\right)^2=\left(2x-3y-1\right)^2=0\)

<=>\(x+2y-4=2x-3y-1=0\)

\(x+2y-4=0\Leftrightarrow x+2y=4\Leftrightarrow2\left(x+2y\right)=8\Leftrightarrow2x+4y=8\)

\(2x-3y-1=0\Leftrightarrow2x-3y=1\)

=>\(\left(2x-3y\right)-\left(2x+4y\right)=1-8\)

=>\(2x-3y-2x-4y=-7\)

=>\(-7y=-7\)=>\(y=1\)=>\(x=2\)

Vậy .............................

Bình luận (0)
Trịnh Xuân Diện
16 tháng 12 2016 lúc 15:02

=>x+2y-4=0 và 2x -3y-1=0

rồi tự tính

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN